Assessing the Authors and Source Impact of Financial Literacy: A Bibliometric Analysis Using R - Rudy Ansar; Brahim Chekima; Suddin Lada; Lim, Ming Fook; Mohamed Bouteraa; Mohd Noor Hidayat Jumainal; Maulana Amirul Adha (Macrothink Institute, 2023)
Using a bibliometric analysis, the goal of this review is to assess and systematically document the author and source's impact on the area of financial literacy. Using R Studio, information is compiled from Scopus databases and analysed. We gathered a searchable database of the 1737 most relevant papers from 2018 to 2022. Assuming the trend continues, the number of publications dedicated to financial literacy is expected to rise between 2018 and 2022. During that period, it was seen that the authors and journals contributed significant impact with a high reputation. The most influential authors and sources on the topic are identified by the bibliometric analysis done using R. It demonstrates the writers’ comprehensive knowledge and grasp of their speciality topic. Furthermore, it aids readers in determining the most relevant source for future study of the scientific and empirical article.